Struktur Morfologi Tanaman Porang (Amorphophallus muelleri ) Pada Habitat Desa Sribunga Kecamatan Buay Pemuka Bangsa Raja Kab Oku Timur - Mutiara, Dian; Rosanti, Dewi (Indobiosains, 2025)
Research on the morphological structure of porang plants growing in Sribunga Village, Buay Pemuka Bangsa Raja District, East Oku Regency was carried out in This research was carried out from March to June 2024. The porang plants (Amorphophallus muelleri) studied were taken from community plantations in Sribunga Village, Buay District Leaders of the Raja Nation of East Oku Regency. Examination of morphological characteristics was carried out at the Biology Laboratory, Faculty of Science and Technology, PGRI University, Palembang. The research uses a survey method. Data analysis includes the basic structure of plants, namely roots, leaves, stems and plant modifications. The morphology of the porang plant (Amorpophallus muellery) has a fibrous root system (radix adventitia). The stem (caulis) has a false stem which is modified into a root tuber. The leaves (folium) are finger-shaped compound leaves. The flowers (flos) are compound cob flowers (spadix) with large reddish bracts (spatha).